2016
DOI: 10.1186/s12913-016-1886-4
|View full text |Cite
|
Sign up to set email alerts
|

Costs of conservative management of early-stage prostate cancer compared to radical prostatectomy–a claims data analysis

Abstract: BackgroundDue to widespread PSA testing incidence rates of localized prostate cancer increase but curative treatment is often not required. Overtreatment imposes a substantial economic burden on health care systems. We compared the direct medical costs of conservative management and radical therapy for the management of early-stage prostate cancer in routine care.MethodsAn observational study design is chosen based on claims data of a German statutory health insurance fund for the years 2008–2011. Three hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…to compared cryotherapy with brachytherapy and found that the cost of cryotherapy was $12 629 (reported in 2008 dollar value). The literature also suggests that conservative management is the least expensive option when compared to the other active treatments . The lower cost estimates for conservative management may be due to lower rates of side effects or no involvement of surgical techniques as in cryotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…to compared cryotherapy with brachytherapy and found that the cost of cryotherapy was $12 629 (reported in 2008 dollar value). The literature also suggests that conservative management is the least expensive option when compared to the other active treatments . The lower cost estimates for conservative management may be due to lower rates of side effects or no involvement of surgical techniques as in cryotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The costs associated with terminal phases of care were the highest in both cohorts. The costs of treatment in cancer are projected to rise with increasing number of cases among older adults, higher survival rates and increasing costs of therapies . A recent international commission suggested that one of the ways to reduce cancer care costs is to improve end‐of‐life care or terminal care .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations